Influence of N‐vinyl‐2‐pyrrolidone and methacrylic acid on thermal curing process of 2‐hydroxyethyl methacrylate hydrogel. Issue 17 (16th October 2019) - Lee, Jung Hyun; Youm, Je Sung; Ju, Hyoung Tae; Kim, Jeong Cheol
ABSTRACT: This study investigated the effects of N ‐vinyl‐2‐pyrrolidone (NVP) and methacrylic acid (MA) comonomers on the curing characteristics and properties of poly(2‐hydroxyethyl methacrylate) (PHEMA) hydrogel for soft contact lenses. A real‐time temperature measurement system was devised and the exothermic behaviors of hydrogel contact lenses comprising PHEMA, P(HEMA/NVP), and P(HEMA/MA) during oven‐curing condition were analyzed. The results of the real‐time temperature measurement were compared with the experimental analysis by using differential scanning calorimetry at different heating rates. NVP and MA content changes affected the HEMA‐based hydrogel's equilibrium water content (EWC), contact lens diameter, and gel fraction. HEMA‐based hydrogel sheets with varying NVP and MA contents were fabricated and mechanically characterized. The temperature at which the exothermic reaction occurred varied depending on the type of added comonomer and the exothermic reaction of HEMA containing NVP was delayed. When NVP was added, the mechanical strength and EWC were lower than when MA was added. In order to maintain the mechanical properties while improving the equilibrium moisture content of the lens, it was found that the use of MA is more advantageous than the use of NVP. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48622. Abstract :